Phosphorylation of INF2 by AMPK promotes mitochondrial fission and oncogenic function in endometrial cancer - Ding, Yan; Lv, Zeheng; Cao, Wenxin; Shi, Wenming; He, Qizhi; Gao, Kun (Cell death & disease, 2024)
Mitochondria are highly dynamic organelles capable of altering their sizes and shapes to maintain metabolic balance through coordinated fission and fusion processes. In various cancer types, mitochondrial hyperfragmentation has been frequently observed, contributing to the progression of cancer toward metastasis. Inverted formin 2 (INF2), which resides in the endoplasmic reticulum (ER), has been found to accelerate actin polymerization and drive mitochondrial fission. In this study, we demonstrate that INF2 expression is significantly upregulated in endometrial cancer (EC) and is associated with a poor prognosis in EC patients. INF2 promotes anchorage-dependent and independent EC cell growth in part by facilitating mitochondrial fission. Furthermore, in conditions of energy stress, AMP-activated protein kinase (AMPK) phosphorylates INF2 at Ser1077, leading to increased localization of INF2 to the ER and enhanced recruitment of the dynamin-related protein 1 (DRP1) to mitochondria. This AMPK-mediated phosphorylation of INF2 at Ser1077 facilitates mitochondrial division and promotes EC cell growth. Pathological examination using immunohistochemical analyses revealed a positive correlation between AMPK activity and phosphorylated INF2 (Ser1077) in EC specimens. Collectively, our findings uncover novel molecular mechanisms involving the AMPK-INF2 axis, which regulates mitochondrial dynamics and malignant cell growth in EC.